STEPHANORHINUS ETRUSCUS (FALCONER, 1868) FROM PIRRO NORD (APRICENA, FOGGIA, SOUTHERN ITALY) WITH NOTES ON THE OTHER LATE EARLY PLEISTOCENE RHINOCEROS REMAINS OF ITALY - LUCA PANDOLFI; CARMELO PETRONIO (Rivista Italiana di Paleontologia e Stratigrafia, 2011)
During the late Early Pleistocene (latest Villafranchian-earliest Galerian), a marked faunal turnover occurred in Italy, with a progressive disappearance of Villafranchian species and the gradual arrival of new species that later characterized the Middle Pleistocene. Two rhinoceros species are reported during this time: Stephanorhinus etruscus and S. hundsheimensis. The morphological and morphometrical analysis of the rhinoceros remains unearthed in the quarries of Pirro Nord (Pirro Faunal Unit, about 1.3-1.6 My) show a great affinity with S. etruscus, in particular with its second evolutionary stage. This stage is characterized by a general variation in body size and proportions. Other rhinoceros remains, found in Italian sites chronologically correlated with Pirro Faunal Unit (FU), are also ascribed to the second evolutionary stage of S. etruscus. In addition, in Italy, the presence of S. hundsheimensis is unknown before the Colle Curti FU (about 1 My). This is likely related to the scarcity of sites chronologically referable to the Early-Middle Pleistocene transition or to a delay in the dispersal event of this species in Italy. Furthermore, the occurrence of S. hundsheimensis in Europe and in Italy may be related to the climatic deterioration of the latest Early Pleistocene, as may be the variation in proportions and size of S. etruscus.